An economic analysis of prenatal cytogenetic technologies for sonographically detected fetal anomalies. Issue 5 (24th March 2014) - Harper, Lorie M.; Sutton, Amelia L.M.; Longman, Ryan E.; Odibo, Anthony O.
<x xml:space="preserve">Abstract</x> When congenital anomalies are diagnosed on prenatal ultrasound, the current standard of care is to perform G‐banded karyotyping on cultured amniotic cells. Chromosomal microarray (CMA) can detect smaller genomic deletions and duplications than traditional karyotype analysis. CMA is the first‐tier test in the postnatal evaluation of children with multiple congenital anomalies. Recent studies have demonstrated the utility of CMA in the prenatal setting and have advocated for widespread implementation of this technology as the preferred test in prenatal diagnosis. However, CMA remains significantly more expensive than karyotype. In this study, we performed an economic analysis of cytogenetic technologies in the prenatal diagnosis of sonographically detected fetal anomalies comparing four strategies: (i) karyotype alone, (ii) CMA alone, (iii) karyotype and CMA, and (iv) karyotype followed by CMA if the karyotype was normal. In a theoretical cohort of 1, 000 patients, CMA alone and karyotype followed by CMA if the karyotype was normal identified a similar number of chromosomal abnormalities. In this model, CMA alone was the most cost‐effective strategy, although karyotype alone and CMA following a normal karyotype are both acceptable alternatives. This study supports the clinical utility of CMA in the prenatal diagnosis of sonographically detected fetal anomalies. © 2014 Wiley Periodicals, Inc.